Inhibition of IgE binding to cross‐reactive carbohydrate determinants enhances diagnostic selectivity. Issue 10 (21st September 2013) - Holzweber, F.; Svehla, E.; Fellner, W.; Dalik, T.; Stubler, S.; Hemmer, W.; Altmann, F.
Abstract Background Allergy diagnosis by determination of allergen‐specific IgE is complicated by clinically irrelevant IgE, of which the most prominent example is IgE against cross‐reactive carbohydrate determinants (CCDs) that occur on allergens from plants and insects. Therefore, CCDs cause numerous false‐positive results. Inhibition of CCDs has been proposed as a remedy, but has not yet found its way into the routine diagnostic laboratory. We sought to provide a simple and affordable procedure to overcome the CCD problem. Methods Serum samples from allergic patients were analysed for allergen‐specific IgEs by different commercial tests (from Mediwiss, Phadia and Siemens) with and without a semisynthetic CCD blocker with minimized potential for nonspecific interactions that was prepared from purified bromelain glycopeptides and human serum albumin. Results Twenty two per cent of about 6000 serum samples reacted with CCD reporter proteins. The incidence of anti‐CCD IgE reached 35% in the teenage group. In patients with anti‐CCD IgE, application of the CCD blocker led to a clear reduction in read‐out values, often below the threshold level. A much better correlation between laboratory results and anamnesis and skin tests was achieved in many cases. The CCD blocker did not affect test results where CCDs were not involved. Conclusion Eliminating the effect of IgEs directed against CCDs by inhibition leads to a significant reduction in false‐positive in vitro test results without lowering sensitivity towards relevant sensitizations. Application of the CCD blocker may be worthwhile wherever natural allergen extracts or components are used.